Sex reversal of red tilapia using 17α-methyltestosterone-enriched feed and increased temperature - Safira Qisthina Ayuningtyas; Muhammad Zairin Junior; Dinar Tri Soelistyowati (Jurnal Akuakultur Indonesia)
ABSTRACT